Re-Innovation of Learner-Centered Pedagogy in Tanzania's Secondary Schools. Issue 3 (October 2019) - Msonde, Sydney Enock; Msonde, Charles Enock
Although learner-centered instruction (LCI) is at the heart of many curriculum innovations in the world, its implementation has generally lacked the kind prominence it deserves. The current study explores how learning study can develop teachers' professional capabilities to practice LCI. Using interviews, lesson preparatory meetings, teachers' reflective journals, and classroom observations, the study employed the phenomenographic variation framework and coding strategies to analyze the resultant data. The results demonstrate that the teachers' understanding of LCI morphed from considering it as a methodological orientation to an object of learning. Therefore, engaging teachers in learning study may bring out valuable pedagogical innovations essential in boosting both the job performance and quality of teaching and learning outcomes.